Uma proposta de sequência didática sobre a Teoria da Relatividade Restrita: perspectivas e avaliações dos professores de física do ensino médio - Batista, Carla Fernanda (Universidade Federal de São Carlos, 2016)
Currently, we live surrounded by technology everywhere, which makes knowledge of Modern and Contemporary Physics indispensable. Researchers justify the importance of incorporating these contents into high school education, but there is a scarcity of studies addressing the methods that should be applied in the classroom. For this reason, this study develops research on the development of a didactic sequence of the Theory of Special Relativity in Zabala's conception, which high school Physics teachers analyzed for its suitability, as well as identifying potential contributions and limitations. The research also examines whether the contents of Modern and Contemporary Physics are addressed in the classroom, whether teachers are prepared to teach these subjects, what methodologies they use, and whether they have any limitations in their approach. The research methodology is qualitative. To achieve the intended objectives, three stages were carried out: the first stage was an interview, with the objective of establishing initial contact with the teachers and gathering information about them; the second stage involved delivering the sequence along with a framework containing guiding questions to assist teachers in analyzing it; and the third stage consisted of collecting the analyzed sequence and recording the responses to the guiding questions. The purpose of this stage was to gather further information regarding the analysis. All interviews were recorded and subsequently transcribed and analyzed. The analysis of the interview transcriptions was conducted using the assumptions of Content Analysis. Through this analysis, it was observed that teachers are in favor of integrating Modern and Contemporary Physics into high school education. However, when it comes to the specific topic of the Theory of Special Relativity, some claim that it would not be feasible. Some of these teachers do not address Modern and Contemporary Physics, and consequently, they do not cover the Theory of Special Relativity in the classroom, which may be related to the fact that these topics are not included in the curriculum of the state of São Paulo. Some of them also stated that they are not equipped to teach these subjects. Therefore, it can be concluded that the integration of Modern and Contemporary Physics is still a controversial subject, as some teachers find it viable while others do not. Thus, further research and analysis are necessary on a larger scale, as incorporating these topics would support both the initial and continuing education of teachers, as well as the organization of the curriculum itself.
A proposal for a didactic sequence on the Special Theory of Relativity: perspectives and evaluations of high school physics teachers
Keywords: Ensino de física moderna; Relatividade restrita; Sequência didática; Teaching of modern physics; Special relativity; Didactic sequence; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL